2017
DOI: 10.1038/nature24482
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of chemical modifications in the human 80S ribosome structure

Abstract: Chemical modifications of human ribosomal RNA (rRNA) are introduced during biogenesis and have been implicated in the dysregulation of protein synthesis, as is found in cancer and other diseases. However, their role in this phenomenon is unknown. Here we visualize more than 130 individual rRNA modifications in the three-dimensional structure of the human ribosome, explaining their structural and functional roles. In addition to a small number of universally conserved sites, we identify many eukaryote- or human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
371
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 297 publications
(399 citation statements)
references
References 70 publications
16
371
2
3
Order By: Relevance
“…This hypothesis has been proposed before on several occasions [45,80,102], and takes special relevance due to the functional and overall structural conservation of mitoribosomes versus ribosomes of other compartments and species, especially because the mitochondrial proteome is more restricted in number and diversity of its components. Furthermore, with the advent and optimisation of high throughput, transcriptome-wide techniques for the targeted detection of RNA modifications, as well as cryoEM [205], it will be now possible to dive to greater depths of biological detail and identify novel modified residues in mt-rRNA. For instance, in addition to the well-established aforementioned residues (Section 2), several novel m 1 A sites were recently reported for mt-rRNAs, which need to be given attention, not only in terms of verification, but also regarding the enzymes involved in their deposition and their functional relevance [201].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…This hypothesis has been proposed before on several occasions [45,80,102], and takes special relevance due to the functional and overall structural conservation of mitoribosomes versus ribosomes of other compartments and species, especially because the mitochondrial proteome is more restricted in number and diversity of its components. Furthermore, with the advent and optimisation of high throughput, transcriptome-wide techniques for the targeted detection of RNA modifications, as well as cryoEM [205], it will be now possible to dive to greater depths of biological detail and identify novel modified residues in mt-rRNA. For instance, in addition to the well-established aforementioned residues (Section 2), several novel m 1 A sites were recently reported for mt-rRNAs, which need to be given attention, not only in terms of verification, but also regarding the enzymes involved in their deposition and their functional relevance [201].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Indeed, a recent study confirmed the presence of m5C in human rRNAs, although its biological role remains unclear. 38 It has been demonstrated that NOP2 possesses m5C methyltransferase capability in yeast. 13 Because NOP2 depletion reduced rRNA abundance in preimplantation embryos, we sought to ask if the methyltransferase activity of NOP2 is responsible for its regulation on rRNA and essential for embryo development.…”
Section: Methyltransferase Activity Ofmentioning
confidence: 99%
“…Angereicherte und abgereicherte Peaks wurden identifiziert und ihre Positionen mit bekannten Methylierungsstellen in humaner rRNAv erglichen (Abbildung 3B,T abelle S2, Abbildung S14). [20]…”
Section: Angewandte Chemieunclassified